Chordomas and chondrosarcomas—The role of radiation therapy. Issue 5 (19th October 2016) - De Amorim Bernstein, Karen; DeLaney, Thomas
Abstract : Achieving negative surgical margins can be challenging for skull base and spinal/paraspinal sarcomas. Data shows that pre‐ or post‐operative radiation therapy improves local control. Delivery of sufficient dose of radiation can be difficult because of the proximity to normal organs/tissues that are sensitive to radiation therapy and therefore dose‐limiting. A comprehensive literature search was conducted using PubMed search engine. The scarcity of prospective, randomized data limits the ability to generate definitive treatment recommendations. J. Surg. Oncol. 2016;114:564–569 . © 2016 Wiley Periodicals, Inc.